Influence of machine generated potting mixture in the growth of black pepper (Piper nigrum L.) cuttings and nutmeg (Myristica fragrans Houtt.) seedlings in nursery - M. Muthamil Selvan, C.K. Thankamani; E. Jayashree, S.J.K. Annamalai (Journal of Plantation Crops, 2017)
-